MEMAYU HAYUNING BAWANA: MEMAHAMI ESENSI GOTONG ROYONG DALAM NILAI KEARIFAN LOKAL MASYARAKAT JAWA - Noorzeha, Fuad; Lasiyo (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
The view that humans are social creatures has now shifted to anti-social humans. Technological advances make humans abandon direct interaction in social life. The presence of technology also makes social relations between individuals and communities replaced with wireless networks. The role of parents in educating children has also changed. Although social interaction is now becoming easier and instantaneous, there is no essence of social interaction itself. Gotong Royong is one of the alternative activities that need to be preserved by the community To improve human status as social creatures. In addition, these activities can foster togetherness in building the sustainability of micro cosmos and macro cosmos in human life in the world. The purpose of this study is to affirm the function and benefits of Gotong Royong in human experience through awareness of the saying